Раскопки стоянки Мира под Запорожьем в 2008 г. - Степанчук, В.Н.; Рыжов, С.Н.; Пудовкина, А.С.; Писарев, И.Б. (Археологічні дослідження в Україні, 2009)
In 2008, at the multilayer Palaeolithic site of Mira, near Zaporizzhya, the areas adjacent to the dwelling structure 1 from the east were studied. The probable evidence has been obtained that the main fireplace was situated outside the dwelling. The new data on micro-stratigraphy and peculiarities of planning have been obtained, as well as additional series of stone artefacts and remains of animals have been revealed.